Lexical and Syntactic Complexities in Undergraduate Students’ Research Articles and Their Correlations to Their Quality - Ratna Dewi (Pascasarjana UM, 2017)
Abstract: This study aims to find out the employment of lexical and syntactic complexities in the undergraduate students’ research articles and their correlations to their quality. It employes a quantitative design through corpus based analysis and correlation analysis using Pearson product-moment correlation coefficient. The results show that lexical density, lexical sophistication, and lexical variation are high except for verb variation, noun variation, adjective variation, adverb variation and modifier variation and the sentence complexity is also high. The quality of the udergraduate students’ research articles is categorized as above good or it is only a half point needed to achieve the criteria of great research article. This research find that there is no correlation between lexical and syntactic complexities with the quality of artiles. It is expected that this article could provide information about the lexical and syntacti complexities which are needed to be improved in the undergraduate students’ research articles.Key Words: lexical complexity, syntactic complexity, article qualityAbstrak: Penelitian ini bertujuan untuk mengetahui penggunaan kompleksitas leksikal dan sintaksis pada artikel penelitian mahasiswa dan korelasinya terhadap kualitasnya. Penelitian ini menggunakan desain kuantitatif melalui analisis berbasis korpus dan analisis korelasi menggunakan koefisien korelasi momen produk Pearson. Hasil penelitian ini menunjukkan bahwa kepadatan leksikal, kecanggihan leksikal, dan variasi leksikal tinggi kecuali pada variasi verba, variasi kata benda, variasi kata sifat, variasi adverbia dan variasi pengubah dan kompleksitas kalimat juga tinggi. Kualitas artikel penelitian mahasiswa tingkat sarjana dikategorikan sangat baik atau hanya setengah poin yang dibutuhkan untuk mencapai kriteria penelitian besar. Penelitian ini menemukan bahwa tidak ada korelasi antara kompleksitas leksikal dan sintaksis dengan kualitas artikel. Diharapkan artikel ini dapat memberikan informasi tentang leksikal dan kompleksitas sintaksis yang perlu ditingkatkan dalam artikel penelitian mahasiswa.Kata kunci: kompleksitas leksikal, kompleksitas sintaksis, kualitas artikel